2016
DOI: 10.1161/strokeaha.115.010835
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Cell Senescence Contributes to Blood–Brain Barrier Breakdown

Abstract: Background and Purpose Age-related changes in the cerebrovasculature, including blood-brain barrier (BBB) disruption, are emerging as potential risks for diverse neurological conditions. Since the accumulation of senescent cells in tissues is increasingly recognized as a critical step leading to age-related organ dysfunction, we evaluated whether senescent vascular cells are associated with compromised BBB integrity. Methods Effects of vascular cell senescence on tight junction (TJ) and barrier integrity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
170
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(174 citation statements)
references
References 45 publications
4
170
0
Order By: Relevance
“…This notwithstanding, age-associated microvascular changes have been implicated in Alzheimer's disease (AD) and vascular dementia [26]. These changes have been suggested to influence the nature and function of the BBB [27,28]. They include loss of junctional complexes, inflammation, cellular damage, and vascular remodeling [29].…”
Section: Discussionmentioning
confidence: 99%
“…This notwithstanding, age-associated microvascular changes have been implicated in Alzheimer's disease (AD) and vascular dementia [26]. These changes have been suggested to influence the nature and function of the BBB [27,28]. They include loss of junctional complexes, inflammation, cellular damage, and vascular remodeling [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence, an irreversible cell cycle process, acts to protect against cancer, and more recently, this process is emerging as a regulator of complex biological processes such as development, tissue repair, and aging (van Deursen, ). For instance, ablation of p16 INK4a reverses the aging phenotype in α‐klotho, an aging suppressor gene, knockout mice (Sato et al, ), and brain Ec are reported as a susceptible cell type in BubR1 hypomorphic‐induced premature senescence mice, confirmed by increased SA‐β‐gal activity and p16 INK4a expression (Yamazaki et al, ). Recently, Baker et al () showed that p16 INK4a positive cells promote age‐dependent changes in organs such as kidney, heart, and fat, but notably these studies excluded lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation and increased EC turnover leads to EC replicative senescence, a cellular state defined by cell cycle arrest (Hornsby, 2010). Accumulation of senescent ECs is associated with disrupted TJs and increased permeability in vitro and in vivo (Yamazaki et al, 2016). Senescent cells typically have a senescence-associated secretory phenotype (SASP), during which production of pro-inflammatory molecules stimulate leukocyte migration, activation and infiltration (Lasry and Ben-Neriah, 2015).…”
Section: Endothelial Cellsmentioning
confidence: 99%